The clinical effectiveness and cost-effectiveness of low-intensity psychological interventions for the secondary prevention of relapse after depression: a systematic review - M Rodgers; M Asaria; S Walker; D McMillan; M Lucock; M Harden; S Palmer; A Eastwood (Health Technology Assessment, 2012)
Background: Depression is the most common mental disorder in community settings and a major cause of disability across the world. The objective of treatment is to achieve remission or at least adequate control of depressive symptoms; however, even after successful treatment, the risk of relapse after remission is significant. Although the effectiveness of low-intensity interventions has been extensively evaluated to treat primary symptoms of psychological difficulties, there has been substantially less research examining the use of these interventions as a relapse prevention strategy. Objective: To systematically review the clinical effectiveness and cost-effectiveness of low-intensity psychological or psychosocial interventions to prevent relapse or recurrence in patients with depression. As the broader definition of ‘low-intensity’ psychological intervention is somewhat contested, the review was conducted in two parts: A, a systematic review of all evaluations of ‘low-intensity’ interventions that were delivered by para-professionals, peer supporters or psychological well-being practitioners as defined by the Improving Access to Psychological Therapies programme; and B, a scoping review of relevant evaluations of interventions involving qualified mental health professionals (e.g. psychiatrists, clinical psychologists, cognitive behavioural therapists) involving < 6 hours of contact per patient. Data sources: Comprehensive literature searches were developed; electronic databases were searched from inception until September 2010 (including MEDLINE, MEDLINE In-Process & Other Non-Indexed Citations, PsycINFO, EMBASE, The Cochrane Library), internet resources were used to identify guidelines on the treatment of depression, and the bibliographies of relevant reviews, guidelines and included studies were scrutinised. Review methods: Two reviewers independently screened titles and abstracts; data were extracted independently by one reviewer using a standardised data extraction form and checked by another. Discrepancies were resolved by consensus, with involvement of a third reviewer when necessary. The inclusion criteria were population – adults or adolescents who had received treatment for depression; intervention – part A, low-intensity interventions, specifically any unsupported psychological/psychosocial interventions or any supported interventions that did not involve highly qualified mental health professionals, and, part B, interventions carried out by qualified mental health professionals that involved < 6 hours of contact per patient; comparator – any, including no treatment, placebo, psychological or pharmacological interventions; outcomes – relapse or recurrence, other outcomes (e.g. social function, quality of life) were recorded where reported; and study design – for clinical effectiveness, randomised, quasi-randomised and non-randomised studies with concurrent control patients. For cost-effectiveness, full economic evaluations that compared two or more treatment options and considered both costs and consequences. No studies met the main part A inclusion criteria. Results: For the clinical effectiveness review, 17 studies (14 completed, three ongoing), reported in 27 publications, met the part B inclusion criteria. These studies were clinically and methodologically diverse, and reported differing degrees of efficacy for the evaluated interventions. One randomised controlled trial (RCT), which evaluated a collaborative care-type programme, was potentially relevant to part A; this study reported no difference between patients receiving the intervention and those receiving usual care in terms of relapse of depression over 12 months. For the cost-effectiveness review, two studies met the criteria for part B. One of these was an economic evaluation of the RCT above, which was potentially relevant to part A. This evaluation found that the intervention may be a cost-effective use of resources when compared with usual care; however, it was unclear how valid these estimates were for the NHS. Limitations: Although any definition of ‘brief’ is likely to be somewhat arbitrary, an inclusion threshold of 6 hours contact per patient was used to select brief high-intensity intervention studies. Most excluded studies evaluated clearly resource-intensive interventions, though occasionally, studies were excluded on the basis of having only slightly more than 6 hours contact per patient. Conclusions: There is inadequate evidence to determine the clinical effectiveness or cost-effectiveness of low-intensity interventions for the prevention of relapse or recurrence of depression. A scoping review of brief high-intensity therapies indicates that some approaches have shown promise in some studies, but findings have not been consistent. Many uncertainties remain and further primary research is required. Careful consideration should be given to the scope of such research; it is important to evaluate the broader patient pathway accounting for the heterogeneous patient groups of interest. Future RCTs conducted in a UK primary care setting should include adult participants in remission or recovery from depression, and evaluate the quality of the intervention and consistency of delivery across practitioners where appropriate. The occurrence of relapse or recurrence should be measured using established methods, and functional outcomes as well as symptoms should be measured; data on quality of life using a generic instrument, such as the European Quality of Life-5 Dimensions (EQ-5D), should be collected. Funding: The National Institute for Health Research Health Technology Assessment programme.